PENGEMBANGAN KOMIK DIGITAL CHLOROPHYL SEBAGAI MEDIA PEMBELAJARAN PEDULI LINGKUNGAN SISWA SMA - BACHTIAR ADI SAPUTRA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The loss of a sense of responsibility that students have towards protecting and preserving nature is also a bad impact of the progress that has occurred in the present era. Therefore, the researchers took the initiative to develop a valid and practical